Hedonic Pricing Model for Real Property Valuation Via GIS - a review - Aladwan, Zubeida; Ahamad Mohd, Sanusi S. (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Hedonic pricing models in real property valuation have been frequently applied in many research studies and projects since it was introduced by Rosen in 1974. The development of Geographic Information Systems (GIS) in the recent decades has gradually supports the usage of hedonic model in the spatial data pricing model studies.
Keywords: real property valuation; building variables; regression analysis; hedonic pricing model; GIS; wycena nieruchomości; budowanie zmiennych; analiza regresji; model wyceny